EVALUATING THE INFRASTRUCTURE, MEDICAL EQUIPMENT, AND SERVICES IN MULTI-SPECIALTY HOSPITALS OF NAGPUR FOR ENHANCED HEALTHCARE DELIVERY - Rathod, Ishwar Mannu; Hingane, Kavita B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the quality of the buildings, healthcare equipments and services in the multi-specialty hospitals in Nagpur. The aim is to determine whether these hospitals have it all, they require to provide a good treatment to people. We employed the help of surveys and interviews that helped us to capture data of the doctors, hospital staffs and the patients. The findings reveal that there is a great difference between the hospitals, some of them being well maintained and equipped and even others having a lot to be done. This research assists us to get an idea on where improvements have to be made so that healthcare can be improved and made effective in Nagpur.